On Retrieving the Baby - Kandiah, Thiru; Singh, Rajendra (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn his recent critique of contemporary Translation Theory (TT), Singh (2005) argues that (1) as things stand, contemporary TT is not really a theory of translation but an exploration that seems to simply assume that the various uses, literal and metaphorical, of the word ‘translation’ and of the techniques employed in what languages normally refer to as translation delimit an interesting domain of which one can construct a theory and (2) one of the new ways in which translation and TT need to be conceptualized is to revisit and renew the old ways in which they used to be seen, albeit with a difference. This paper will, in effect, sketch out a possible itinerary for such a revisit. The purpose of this paper is, in other words, to summarize that critique and to sketch out the content of what we view as crucial courses for a programme in translation that could constitute the first proactive steps for recovering the baby contemporary TT seems to have thrown out with the bath water of structuralist ‘equivalence’. These courses have been and are being tried at the newly instituted graduate programme in translation at the University of Peradeniya in Srilanka.